2015
DOI: 10.1016/j.jsps.2015.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of dissolution rate of class II drugs (Hydrochlorothiazide); a comparative study of the two novel approaches; solid dispersion and liqui-solid techniques

Abstract: Liqui-solid technique and solid dispersion formation are two novel approaches for enhancement of dissolution rate of BCS class II drugs. Liqui-solid compact converts a liquid drug or drug solution into a free flowing powder with enhanced dissolution rate. In case of solid dispersion drug is molecularly dispersed in a hydrophilic polymer in solid state. In the present study, Liqui-solid and solid dispersion techniques were applied to enhance the dissolution of the Hydrochlorothiazide. Three formulations of Hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 5 publications
0
17
0
2
Order By: Relevance
“…There is not agreement in the classification criterion of HCTZ, according to the Biopharmaceutical Classification System (BCS) (3). Some authors consider it as a Class IV or II drug (4,5). However, most authors classify HCTZ as a Class III drug (i.e., high solubility and low permeability) (3,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…There is not agreement in the classification criterion of HCTZ, according to the Biopharmaceutical Classification System (BCS) (3). Some authors consider it as a Class IV or II drug (4,5). However, most authors classify HCTZ as a Class III drug (i.e., high solubility and low permeability) (3,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Compacts of LS-2 represented the lowest MDT and highest %DE compared with other prepared LS formulations and it was considered as the optimum LS formula. In addition, LS-2 compacts showed better improvement in dissolution in contrast with DCT and marketed tablets (PlavixÂź) since, lower MDT and higher %DE values indicated that, LS-2 compacts were significantly (p < 0.05) enhanced dissolution rate (42) .…”
Section: Weight Variationmentioning
confidence: 93%
“…Pelelehan merupakan metode yang paling banyak digunakan karena ramah lingkungan, biaya efektif, dan jarang ditemukan adanya masalah stabilitas dan toksisitas 8 . Penggunaan polimer hidrofilik pada sistem dispersi padat secara signifikan dapat meningkatkan laju disolusi obat yang terdispersi dalam matriks pada tingkat molekuler dibandingkan tanpa penggunaan polimer 10 . Penggunaan dekstrosa pada dispersi padat menunjukkan laju disolusi yang lebih tinggi jika dibandingkan dengan polimer hidrofilik lain yaitu manitol dan urea 11 .…”
Section: Pendahuluanunclassified